ANALYSIS OF IMMUNOHISTOCHEMICAL EXPRESSION OF P16INK4a IN NEOPLASTIC SQUAMOUS CELL LESIONS OF CERVIX - Mohan, Dr. K.R.; Sasikala, Dr. S.; Ravi, Dr. S.; Sagunthala, Dr. P.; Sathish Kumar, Dr. I.Vijay (International Journal of Innovative Research in Medical Science, 2016)
Introduction: Cervical cancer is caused by persistent infection by high risk Human papilloma virus (HPV).Increasing expression of HPV viral oncogenes might be reflected by increased expression of p16. Hence immunohistochemical detection of p16INK4a is an easy and cost effective method than molecular detection of HPV. Aims: The purpose of this study were to evaluate the results of expression of p16INK4a in neoplastic squamous cell lesions of cervix in order to assess the association of HPV infection in those lesions and to study the pattern of expression of p16 and also to compare p16 expression in various histological types of cervical neoplastic squamous cell lesions by immunohistochemistry. Methods: Immunohistochemical analysis of p16 expression was performed on 26 paraffin embedded tissue samples, obtained from cervical biopsy including 2 early invasive squamous cell carcinoma (SCC), 6 large cell keratinizing SCC, 16 large cell non- keratinizing SCC and 2 cases small cell non-keratinizing SCC by using commercially available mouse monoclonal antibody to p16 (clone G175 – 405). Two parameters were evaluated in p16 expression: Percentage of p16 positive cells and reaction intensity of p16 immunostaining. The p16 expression was graded as negative; Grade 1, 2, 3 and its reaction intensity was graded as negative, weak, moderate and strong. Results: In the present study out of 26 cases, the incidence of large cell non- keratinizing SCC constituted majority of the neoplastic lesions of cervix (61.5%). Most of the SCC (96.15%) showed grade 3 scoring for p16 positivity except one case which showed grade 2 scoring. Majority of SCC cases (96%) showed strong reaction intensity for p16 immunostaining. Conclusion: In this study of 26 neoplastic sqaumous cell lesions, all patterns of cervical neoplasia showed p16 positivity. P16 may be useful as an adjunct in histological sections to detect HPV in those lesions.